Global perspectives: COVID-19 in the eyes of a physician pharmacologist - Adedapo Adesokan (Inishmore Laser Scientific Publishing Ltd, 2020)
Emergence of global pandemic coronavirus-2019 (COVID-19) has brought the whole world to a standstill. This viewpoint critically appraises factors that have contributed to its huge morbidity and mortality burden worldwide, and proffers solutions. First, the paper examines how drug development scientists and formulation experts could develop novel combination therapies from pre-existing drugs that will disrupt future coronaviruses replication and RNA synthesis. The author discusses the development of novel barrier topical therapies that would prevent the respiratory viruses from gaining entry into host cells. Finally, the article looked at the science of vaccines and why it is the main exit strategy out of this crisis, as well as suggested novel treatment strategies for pharmacologists and clinical scientists globally, particularly in terms of finding new preventive antiviral barrier ointments and possible curative drug treatment.